IMPLEMENTASI â€œGOOD FAITHâ€ PADA PERJANJIAN KERJASAMA ANTARA PERUSAHAAN BEDA NEGARA - Cahyaningtyas, Kartika; Wibowo, Eko Ari (JURNAL SUMBER HUKUM, 2023)
This research examines and analyzes international contracts that do not fulfill the principle of good faith or in Indonesian means Good Faith because the agreement made by the parties is not reached, then there can be disputes between the parties who made the agreement and there could be parties who suffer losses if it arises. the dispute. The legal remedies chosen by the parties making the agreement must be stated in the contents of the agreement. The method used in normative research with a problem approach is the case approach. The research results in the form of Cooperation Agreements between companies from different countries have not implemented the principle of "good faith" in post-contracts in the form of implementing "good faith" so that disputes occur. The legal remedy chosen was also not implemented properly, even though the settlement option came from an agreement stated in the agreement through the Indonesian National Arbitration Board (BANI). It is reasonable to suspect that this settlement option is not pure but because in international contracts the settlement is usually through the Indonesian National Arbitration Board (BANI). The result is that one of the parties feels disadvantaged. Keywords : International Contracts, Good Faith, Indonesian National Arbitration Board (BANI)